Original paperUsefulness of capillaroscopy in assessment of angiogenic vascular changes in psoriasis - Bartosińska, Joanna; Chodorowska, Grażyna; Krasowska, Dorota; Juszkiewicz-Borowiec, Maria; Chodorowski, Jakub; Wawrzycki, Bartłomiej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
Introduction: Capillaroscopy is a non-invasive, well-tolerated, repeatable diagnostic method for intravital assessment of the nutritional part of microcirculation. On capillaroscopic examination some quantitative and qualitative vascular abnormalities resulting from disturbed angiogenesis are visible. Psoriasis is a chronic, inflammatory condition where neovascularisation is the dominant pathogenetic feature. Microvascular changes are predominant in the formation of psoriatic lesions. Aim: The aim of the study was to assess capillaroscopically microvascular changes in psoriatic patients and underline abnormalities resulting from disturbed angiogenesis. Material and methods: The study included 111 adult psoriatic patients (17 female and 94 male), aged 18 to 69, diagnosed with psoriasis, in whom exacerbation of the disease had been observed 2-8 weeks previously. The control group consisted of 30 healthy individuals. Nailfold capillaroscopies of fingers II to V of both hands were performed. Results: The incidence of tortuous nailfold capillaries was significantly different in psoriatic patients in comparison with the healthy group (p=0.018). In psoriatic patients the following nailfold capillaries were observed: coiled (24.32%), of a “psoriasis plaque” type (15.32%), “M-shaped” (18.92%) and branching (10.81%), which was in contrast with the healthy group. In 14.41% of psoriatic patients a decreased number of nailfold capillaries was found, while in the control group the number of nailfold capillaries remained unchanged. Conclusions: Psoriatic patients presented microvascular abnormalities, confirmed by altered capillaroscopic image, in comparison with healthy controls. In capillaroscopically examined patients some characteristic microvascular changes, which may result from disturbed angiogenetic processes, were detected.